Forming organizational culture the future correctional teachers by gaming pedagogical technologies - Яцинік, А. В. (Scientific notes of the pedagogical department, 2018)
The current state of Ukrainian society requires significant changes in all spheres of public life, not only in economic, but also in the system of spiritual values. While the education system is being reformed, democratization of education, the transformation of views on the modern teacher are carried out. Particular attention should be paid to those changes that occur in the organization of teaching children with special educational needs, namely the introduction of inclusive education. Improving the quality of education requires some changes in the professional training of teaching staff. The modernization of the teacher training system is specified not only by changes in the legislation of Ukraine, but also by selected civilizational priorities, commitment to approach European standards. Professional development of the future correctional teacher is provided through the game teaching technologies, based on the game as a kind of students’ activity. During the game the student carries out quasi-professional activity, i.e. the activity which is professional in the form, but the training is based on its results and content. The article deals with the issues of the game emergence and development as one of the leading activities, a comparative analysis of the game and game technology is covered, the characteristic concept of organizational culture is given, the structural components of organizational culture are determined, the feasibility of using gaming technologies in the training of future correctional teachers in higher educational institutions, the necessity of introducing innovative pedagogical technologies into the educational process of a higher educational institution are singled out Prospects for improving the work of educational institutions within the implementation of inclusive education are outlined.